2014
DOI: 10.1175/jcli-d-13-00096.1
|View full text |Cite
|
Sign up to set email alerts
|

An Objective Satellite-Based Tropical Cyclone Size Climatology

Abstract: Storm-centered infrared (IR) imagery of tropical cyclones (TCs) is related to the 850-hPa mean tangential wind at a radius of 500 km (V500) calculated from 6-hourly global numerical analyses for North Atlantic and eastern North Pacific TCs for 1995-2011. V500 estimates are scaled using the climatological vortex decay rate beyond 500 km to estimate the radius of 5 kt (1 kt 5 0.514 m s 21) winds (R5) or TC size. A much larger historical record of TC-centered IR imagery (1978-2011 is then used to estimate TC size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
205
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(226 citation statements)
references
References 50 publications
17
205
4
Order By: Relevance
“…Particularly for coastal communities, the size of the TC wind field can be catastrophic depending on the radius of hurricane-force winds and the duration of the event. In addition, predicting the size of the TC wind field is important to determine the potential impact of storm surge, the spatial scope of issued evacuation orders, and potential extent of wind damage (Brand 1972;Weatherford and Gray 1988a,b;Kimball and Mulekar 2004;Knaff et al 2014). During and subsequent to TC landfall, the structure of the precipitation field is important for predicting the severity of inland freshwater flooding, potential mudslides in complex terrain, and TC-spawned tornadoes from the highly convective outer rainbands.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly for coastal communities, the size of the TC wind field can be catastrophic depending on the radius of hurricane-force winds and the duration of the event. In addition, predicting the size of the TC wind field is important to determine the potential impact of storm surge, the spatial scope of issued evacuation orders, and potential extent of wind damage (Brand 1972;Weatherford and Gray 1988a,b;Kimball and Mulekar 2004;Knaff et al 2014). During and subsequent to TC landfall, the structure of the precipitation field is important for predicting the severity of inland freshwater flooding, potential mudslides in complex terrain, and TC-spawned tornadoes from the highly convective outer rainbands.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the longer tracks generally have higher wind speeds and deeper central pressures (e.g., Kim et al 2011). In our analysis, more intense TCs appear to have a larger storm radius, but TC size is not necessarily correlated with intensity (Weatherford 15 and Gray 1988; Knaff et al 2014). High correlation (correlation coefficient r = 0.58) between size and intensity may be one of the characteristics of TCs that have affected Korea.…”
Section: Resultsmentioning
confidence: 65%
“…The mean of the nine profiles obtained in this region is finally adopted as the optimal one. The Empirical orthogonal function (EOF) analysis is commonly used to extract crucial information from IRBT [7,19,35]. However, here we do not correlate TC intensity directly to IRBT profiles, because by testing the 325 cases we found that taking the EOFs as predicators for intensity contributes very little to improving the regression.…”
Section: Potential Predicators Extractionmentioning
confidence: 94%
“…Therefore, it is necessary to "thin" the initial pool of the potential predictors. Note that for the aim of training an objective method of TC intensity estimation without knowing any information of the TC in advance, any variables that represent TC itself are not included, they had been testified as significant in estimating TC wind structure though [7,8,19,35].…”
Section: Multiple Linear Regression Model Developmentmentioning
confidence: 99%